2016
DOI: 10.21314/jcf.2016.317
|View full text |Cite
|
Sign up to set email alerts
|

Pricing swing options in electricity markets with two stochastic factors using a partial differential equation approach

Abstract: In this paper, we consider the numerical valuation of swing options in electricity markets based on a two-factor model. These kinds of contracts are modeled as pathdependent options with multiple exercise rights. From a mathematical point of view, the valuation of these products is posed as a sequence of free boundary problems, where two exercise rights are separated by a time period. In order to solve the pricing problem, we propose appropriate numerical methods based on a Crank-Nicolson semi-Lagrangian metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…As we use nonparametric methods a closed-form solution cannot be found. Recently, several numerical methods have been developed to solve this kind of problems; see [38,39].…”
Section: Abstract and Applied Analysismentioning
confidence: 99%
“…As we use nonparametric methods a closed-form solution cannot be found. Recently, several numerical methods have been developed to solve this kind of problems; see [38,39].…”
Section: Abstract and Applied Analysismentioning
confidence: 99%
“…In addition, some research results have demonstrated that the character of jumps has a tremendous influence on the value of options. Among these, the jump-diffusion model described more accurately than a Brownian motion [14][15][16][17][18][19][20]. Moreover, some models for describing the underlying asset were the stochastic volatility jump model [21,22], the double stochastic volatility model with jumps [23,24], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we replace the binomial and trinomial trees of Lari et al (2001) and Jaillet et al (2004) with the stochastic trees of Broadie and Glasserman (1997), hence creating the Forest of Stochastic Trees (FOST) method for valuing multiple exercise options. The FOST can be thought of as generalizations of two different methodologies; specifically, it extends valuation and control of energy production and storage facilities Chen and Forsyth (2007); Ludkovski and Carmona (2010); Thompson et al (2009); and (iv) swing options Calvo-Garrido et al (2017); Jaillet et al (2004); Lari et al (2001); Wilhelm and Winter (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Discrete-time tree-based methods for valuing American-style options Cox et al (1979) have been extended to MEOs via the Forest of Trees Jaillet et al (2004); Lari et al (2001). Techniques for pricing American-style options using solutions of PDEs have been modified to MEOs Calvo-Garrido et al (2017); Chen and Forsyth (2007); Thompson et al (2009); Wilhelm and Winter (2008). These methods for MEOs inherit properties similar to the corresponding methods for single-exercise options.…”
Section: Introductionmentioning
confidence: 99%